2015
DOI: 10.1093/nop/npv054
|View full text |Cite
|
Sign up to set email alerts
|

Response of metastatic glioma to vemurafenib

Abstract: Extraneural metastatic disease of glioma is rare and poses unique therapeutic challenges. Increasingly, the ability to sequence genetic alterations in tumors has allowed for the identification of common oncogenic signatures such as the activating BRAFV600E mutation and may be useful in therapeutic decision making. We report two patients with widespread aggressive gliomas whose tumors were found to express the BRAFV600E mutation and then responded robustly albeit transiently when exposed to vemurafenib. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
0
24
0
2
Order By: Relevance
“…With BRAFi/MEKi therapy we encountered an earlier than expected remarkable treatment response that was similar with other reports ( Table 2). Five glioblastoma patients, all of them 40 years old or younger, have been described in the literature where BRAFi monotherapy was given as second line salvage treatment and only one as primary treatment [21,22,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…With BRAFi/MEKi therapy we encountered an earlier than expected remarkable treatment response that was similar with other reports ( Table 2). Five glioblastoma patients, all of them 40 years old or younger, have been described in the literature where BRAFi monotherapy was given as second line salvage treatment and only one as primary treatment [21,22,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…10,[18][19][20][21][22][23][24] In total, adult HGG or GBM cases were composed of 4 GBM/eGBM, 9 aPXA, and 1 anaplastic ganglioglioma, with 10 patients treated with single-agent BRAFi (5 with vemurafenib, 5 with dabrafenib) and 4 treated with combination BRAFi/MEKi (all with dabrafenib + trametinib). With the exception of 2 patients treated in the first-line setting, all others were treated at recurrence.…”
Section: Efficacymentioning
confidence: 99%
“…Second, many of the reports describe rapid clinical improvement after initiating BRAF-targeted therapy. 10,19,21,23 This point is key given that several of the patients described had a poor performance status that precluded more aggressive treatments, such as standard cytotoxic chemotherapy or radiation. Similarly, BRAF inhibitors are generally well tolerated, with manageable side effects.…”
Section: Efficacymentioning
confidence: 99%
“…11 There have been a few cas-es in which targeted treatment with BRAF inhibitors has been successfully attempted, but resistance emerges in a few months, similar to what has been seen in melanoma and other tumor types. [12][13][14] The emergence of resistance over time has been reproduced in preclinical glioma models, 15,16 although these models have also shown that dual inhibition with BRAF and MEK inhibitors can prevent resistance.…”
mentioning
confidence: 99%
“…16 However, to date, case reports in adults with primary brain tumors have only examined BRAF inhibition, resulting in a mix of response and progression (Table 1). 12,14,[22][23][24][25] Whether adding an MEK inhibitor would change the clinical course is unknown. To answer this question, 2 clinical trials evaluating the activity of dabrafenib and trametinib in pediatric patients with recurrent BRAF V600-mutated low-or high-grade gliomas (ClinicalTrials.gov identifiers: NCT02124772 and NCT02684058, respectively) are open or planned to open shortly.…”
mentioning
confidence: 99%